Organization Factors on the Quality of Financial Applications in Insurance Companies - lilis puspitawati (Universitas Pendidikan Indonesia, 2021)
Abstract: This study to find out the magnitude of the organizational environmental factors on the quality of Financial Application in insurance companies. This research is motivated by the problem of the low quality of Financial Applications in several insurance companies in Indonesia, because many financial applications are not integrated and often experience interference. The research used descriptive and qualitative methods. The sample in this study were 35 financial accounting units of insurance companies in Bandung city, which were selected based on the Simple Random Sampling technique. To test the effect between variables, multiple linear regression analysis was used. The results showed that information technology had a significant positive effect on the quality of financial applications, top management support had a significant positive effect on the quality of financial applications and organizational culture had a significant positive effect on the quality of financial applications.